"Conformational lock" via unusual intramolecular C–F⋯OC and C–H⋯Cl–C parallel dipoles observed in in situ cryocrystallized liquids. Issue 45 (5th May 2016) - Dey, Dhananjay; Bhandary, Subhrajyoti; Sirohiwal, Abhishek; Hathwar, Venkatesha R.; Chopra, Deepak
Abstract : This study highlights the unusual features associated with the arrangement of parallel bond dipoles play a role in conformational locking in in situ cryocrystallized liquids. Abstract : We report an unusual intramolecular C–F⋯OC and C–H⋯Cl–C parallel dipole–dipole alignment which "locks" the molecular conformation of cryocrystallized liquids towards planarity where the diatropic ring current establishes the existence of aromaticity in the five-membered ring associated with F⋯O contact. Topological analysis establishes the bonding interaction between [F, O] and [H, Cl].